Strategic Management Approach in Productive Zakat Fund Management for Mustahik Welfare - Faridna Agung Cahyono; Edi Cahyono; Rakotoarisoa Maminirina Fenitra (Journal of Islamic Enterpreneurship and Management, 2025)
This Study aims to know that the influence of productive zakat to success business mustahik with levels generation and background behind family entrepreneur as variables moderation, as well as know the influence of productive zakat and success business​ to welfare, and the influence of productive zakat to welfare mediated success busines. Research This use approach quantitative with do survey through questionnaires given​ to 119 respondents in Central Java. The sampling technique used is purposive sampling. The data analysis technique used in study This is regression linear simple, moderation and mediation. Research results show that zakat is productive, level generation and background behind family entrepreneur influential positive and significant to success business mustahik. Variable levels generation and background behind family entrepreneur capable moderate the influence of productive zakat to success business mustahik. Variables of productive zakat and success business influential positive significant to welfare mustahik, as well as variables success business can mediate productive zakat relationship to welfare mustahik